KONSEP JAKARTA SMART CITY MELALUI JAKI SUPER APP UNTUK MENINGKATKAN PELAYANAN PUBLIK: The Jakarta Smart City Concept Through The JAKI Super App To Improve Public Services - Nabiila Saarah Indah Wibowo; Ferry Edwar (AMICUS CURIAE, 2025)
The authority of the DKI Jakarta Provincial government to implement the Jakarta Smart City concept in an effort to improve public services through the JAKI Super App. By identifying problems, how is the implementation carried out by the Jakarta Provincial Government in implementing the concept of Jakarta Smart City as a form of Public Service in accordance with the Jakarta Governor's Regulation Number 144 of 2019? and what are the obstacles faced by the DKI Jakarta Provincial Government for the 2021-2023 period in improving Public Services through the JakiSuper App? The research type is normative research with descriptive analysis. Literature study is a way of obtaining data. The findings of this research and the conclusion study are that the JAKI application is a breakthrough and leading innovation in the digitization of government health services and one of the most superior regional government applications in Indonesia, Smart City is based on efforts to solve problems experienced by a city, so that the city becomes livable, harmonious and prosperous for the community. to raise living standards in a way that is sustainable manner and support an educated, intelligent and moral society. The DKI Jakarta Provincial Government is maximizing the use of technological advances.